English Vocabulary Pop Quiz Application for Beginner English Learners on Vocabulary Mastery: Students’ Perception - Dini Mutia Havid; Maryati Salmiah (Yayasan Pendidikan Bima Berilmu, 2025)
This study aims to explore beginner english learners’ perceptions of using the English Vocabulary Pop Quiz Application to enhance vocabulary mastery. The research employed a descriptive qualitative approach, utilizing a likert scale questionnaire and semi-structured interviews as instruments. Data were collected from 45 respondents who completed the questionnaire online and five students who participated in follow-up interviews for deeper analysis. The results revealed five major findings. First, enrichment student’ vocabulary indicates that students experienced improved word memorization, recognition, and contextual understanding. Second, increase student’s understanding of vocabulary reflects students’ ability to apply vocabulary accurately in speaking and writing. Third, developing students’ motivation on learning new vocabulary highlights how the app’s game-like structure sustained students’ interest and encouraged consistent vocabulary practice. Fourth, supporting flexible and efficient learning access emphasizes the app’s offline usability and time flexibility, enabling students to study independently and conveniently. Fifth, Expressed Interactive Features on Expressing Literacy and Enjoyment Features demonstrates that students enjoyed the app’s interactive layout, which increased their emotional engagement and literacy involvement. Based on these findings, recommended that teachers and educators consider integrating the English Vocabulary Pop Quiz Application or similar gamified tools into vocabulary instruction for beginner learners. Developers were also encouraged to enhance the app with additional features to maintain user interest and expand learning opportunities.